Pengaruh model pembelajaran RADEC berbantuan powerpoint interaktif terhadap kemampuan numerasi peserta didik sekolah dasar - Fitri, Finca Mandela; Efendi, Ujang; Abung, Miranda; ., Rapani (Didaktika Dwija Indria, 2025)
The issue addressed in this study was the low numeracy skills of fourth-grade students at SD Negeri 5 Metro Pusat. This research aimed to determine the effect of the RADEC learning model supported by interactive Powerpoint on students' numeracy skills. The method used was a quasi-experiment with a non-equivalent control group design. The sampling technique applied was saturated sampling, with a total sample of 54 students. The research instruments consisted of an essay test and a non-test in the form of observation sheets. The data were analyzed using simple linear regression and a t-test, which resulted in a significance value of 0.002 < 0.05, and the t-test showed a significance value of 0.000 < 0.05. The results of the study showed that there was an effect of the RADEC learning model assisted by interactive Powerpoint on students' numeracy abilities, and there was a difference in numeracy abilities between the experimental class and the control class of fourth-grade students at SD Negeri 5 Metro Pusat. The RADEC learning model, enhanced with interactive Powerpoint, effectively helped students understand mathematical concepts by connecting them to real-life contexts, thereby improving their numeracy skills.